Personal Deixis in the Madurese Translation of Surah Yaseen - Adriana, Iswah; Effendy, Moh. Hafid; Ayuanita, Kristanti; Putikadyanto, Agus Purnomo Ahmad; Wulansari, Retno (OKARA: Jurnal Bahasa dan Sastra, 2024)
Accurately interpreting the Qur'an is always challenging, especially within the Madurese translation of Surah Yaseen. Given the linguistic intricacies and the cultural context of Madura's devout Muslim community and its Tahlil tradition, it is necessary to identify and understand personal deixis accurately to avoid misunderstandings and ensure faithful interpretation of the sacred text. This study focuses on various personal deixis in Madurese to identify its forms and references in Surah Yaseen. By employing a qualitative descriptive approach and observational method with advanced note-taking, the study scrutinizes verses bearing personal deixis in the Madurese translation. The research findings reveal several forms of personal deixis: Sèngko' (I/Allah), sèngko' (me/other than Allah), kaulâ (me), Sèngko' (We/Allah), sèngko' kabbhi (us/other than Allah), bâ'na (you), bâ'na kabbhi (all of you), (orèng) jâreya (him), and (rèng-orèng) jâreya (them). Those personal deixes refer to Allah, the Prophet Muhammad, the Arabs, residents of the land of Intakiyah, the apostles of Allah, the unbelievers, Habib an-Najar, and Allah's creatures. The researcher highlights the presence of the same personal deixis form, Sèngko', in both singular and plural first person in Madurese, referring to Allah, which may lead to confusion in comprehension, thus suggesting future translation teams distinguish between the singular and plural forms of "Sèngko'" to avoid confusion among readers.